Bottlenecks of Electoral Violence on Electoral Process and Human Welfare in Kanyama Constituency of Lusaka District, Zambia - Kawila, Eliazer Lushinga; Matole, Adrian; Mulubale, Sanny; Simui, Francis; Muleya, Gistered (Advances in Social Sciences Research Journal, 2023)
This article explored bottlenecks of electoral violence on electoral process and human welfare in Kanyama Constituency of Lusaka District, Zambia. The case study design was employed on a targeted population that comprised of 28 participants. The interview guide was used as a tool for primary data production. The main findings of this research were that violence impacted negatively the electoral process by promoting voter apathy especially among women and those that are physically challenged. It was also found that violence disturbs political self-will for the electorates to make independent decisions. Similarly, it was found that electoral violence creates unbalanced political playing field for the candidates to market themselves to the potential electorates. Equally, it was revealed that electoral violence leads to decline in economic activities, destruction of property and a threat to human life. The article concludes that electoral violence denies electorates an opportunity to elect credible leaders and as such, it should not be condoned. Thus, the article recommends that the Electoral Commission of Zambia (ECZ) should give harsh punishment to those who are fond of engaging in electoral violence as this may deter others from participating in such undemocratic activities.